Revascularization of an Immature Maxillary First Premolar with Necrotic Tissue: A Case Report - Rahbani Nobar, Behnam; Akbarian Rad, Nazila; Ghorbanzade, Sajede; Ghorbanzade, Fatemeh (Journal of Dental School, 2019)
Objectives The purpose of this study was to present a case of regenerative endodontic procedure. Case The maxillary 1st premolar of a 9-year-old patient was diagnosed as necrotic. Since the tooth was immature, we decided to treat this tooth with regenerative endodontic procedure. After disinfection of the canal, bleeding was induced by lacerating the peri-apical tissues and a blood clot was formed. Orifice was sealed by MTA and the tooth was restored. 6-months and 1-year follow-ups showed increased root thickness and closure of the apical. Conclusion It can be concluded that the regenerative endodontic procedure used in this study was successful since there was an evident development in root width.